Sentence skills : a workbook for writers - Langan, John. ([S.l.] : McGraw-Hill, 1997)
This best-selling sentence-level worktext by John Langan continues to help students master the essential grammar, mechanics, punctuation, and usage skills needed for clear, thoughtful writing. The ninth edition of Sentence Skills features new writing assignments, review tests, and references.